1973
DOI: 10.1002/aja.1001370208
|View full text |Cite
|
Sign up to set email alerts
|

Cytological aspects of pineal development in rats and hamsters

Abstract: Evidence has been accumulating which supports the hypothesis that through phylogenetic evolution, the mammalian pinealocyte has evolved from the pineal photoreceptor-cell which is characteristic of certain lower vertebrates. In the present study, developing pineal glands in fetal rats and hamsters were studied at light and electron microscopic levels to determine whether or not the ontogenetic development of pineal cells affords clues to their phylogenetic origin. Pineal development in fetal rats occurs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
32
0
1

Year Published

1977
1977
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 33 publications
7
32
0
1
Order By: Relevance
“…On the other hand, mammalian pinealocytes are morphologically dissimilar to glandular cells and-as already mentioned by WOLFE (1965)-they exhibit some cytological characteristics of photosensory cells. Similar results were obtained for mammalian pinealocytes by CLABOUGH (1973) and ZIMMERMANN and Tso (1975).…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, mammalian pinealocytes are morphologically dissimilar to glandular cells and-as already mentioned by WOLFE (1965)-they exhibit some cytological characteristics of photosensory cells. Similar results were obtained for mammalian pinealocytes by CLABOUGH (1973) and ZIMMERMANN and Tso (1975).…”
Section: Discussionsupporting
confidence: 77%
“…photoreception (Wetterberg et a!., 1970) and, in addition, the pinea! gland may be capable of processing light information, since photoreceptor-like cells are present during the early development of the gland and after birth in rats and hamsters (Clabough, 1973 blinded as well as sighted hamsters. From 7 to 13 weeks of age, intact hamsters on 6L:18D cycles displayed no decline in sex accessory organ size and for the males, only partial gonadal regression.…”
Section: Discussionmentioning
confidence: 99%
“…Pinealocytes of neonatal but not adult rats have photoreceptor-like morphology (19,20). Furthermore, in vitro studies by Araki and colleagues (21)(22)(23)(24) have shown that if neonatal rat pineals are dissociated and cultured, some cells express photoreceptor properties such as rhodopsin immunoreactivity and synthesis of rhodopsin transcript.…”
mentioning
confidence: 99%